2021
DOI: 10.1111/acer.14538
|View full text |Cite
|
Sign up to set email alerts
|

Executive and Social Functioning Across Development in Children and Adolescents With Prenatal Alcohol Exposure

Abstract: Background Prenatal alcohol exposure (PAE) is linked to a variety of neurodevelopmental challenges, including social functioning (SF) and executive functioning (EF) deficits. These deficits present differently across developmental stages from preschool age to adolescence. Methods The post hoc analyses described here were conducted on data from 83 preschool‐age children with PAE (early childhood group; ages 2.5 to 5.0) and 95 adolescents (49 with PAE, 46 controls; ages 8 to 16). Each child completed EF tasks as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 59 publications
0
9
0
1
Order By: Relevance
“…Specifically, trajectories that converge towards typicality predict better clinical outcomes in large, longitudinal samples of children diagnosed with autism (Andrews et al, 2021 ; Ecker et al, 2010 ; Tunç et al, 2019 ) and ADHD (Shaw et al, 2006 ). Further studies are needed to investigate whether atypical trajectories of white matter tracts, such as those seen here, coincide with the progression of neurodevelopmental challenges in young children with PAE (Hanlon‐Dearman et al, 2020 ; Rockhold et al, 2020 ; Subramoney et al, 2018 ). For example, the onset of challenges may relate to the distinct trajectories of early maturing tracts (e.g., ILF, IFOF) compared to later maturing tracts (e.g., uncinate fasciculus) (Reynolds et al, 2019 ) .…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Specifically, trajectories that converge towards typicality predict better clinical outcomes in large, longitudinal samples of children diagnosed with autism (Andrews et al, 2021 ; Ecker et al, 2010 ; Tunç et al, 2019 ) and ADHD (Shaw et al, 2006 ). Further studies are needed to investigate whether atypical trajectories of white matter tracts, such as those seen here, coincide with the progression of neurodevelopmental challenges in young children with PAE (Hanlon‐Dearman et al, 2020 ; Rockhold et al, 2020 ; Subramoney et al, 2018 ). For example, the onset of challenges may relate to the distinct trajectories of early maturing tracts (e.g., ILF, IFOF) compared to later maturing tracts (e.g., uncinate fasciculus) (Reynolds et al, 2019 ) .…”
Section: Discussionmentioning
confidence: 91%
“…This highlights the importance of our longitudinal analysis and the need for future longitudinal studies around PAE. Specifically, trajectories that converge towards typicality predict better clinical outcomes in large, longitudinal samples of children diagnosed with autism (Andrews et al, 2021;Ecker et al, 2010;Tunç et al, 2019) and ADHD (Shaw et al, 2006) Rockhold et al, 2020;Subramoney et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, structural changes in brain formation have been linked to impaired behavior and cognition (Nuñez & Sowell, 2011; Riley & McGee, 2005). Individuals with FASD demonstrate impaired social functioning (Rockhold et al, 2021). Data from animal models also strongly suggest that embryonic ethanol exposure alters social behavior (Kelly et al, 2009).…”
Section: Zebrafish Insights Into Ethanol Teratogenicitymentioning
confidence: 99%
“…In terms of reproductive development, early fetal development involves a series of intricate regulations and cell divisions, which make it very sensitive to external interference. Some external factors may not have obvious effects on healthy adults but would cause irreversible effects on embryonic development [Rockhold et al, 2021]. A study showed that Gadolinium MRI with 1.5 or 3 T SMFs during pregnancy was associated with an increased risk of rheumatism, inflammation, infiltrative skin conditions, stillbirth, or neonatal death [Ray et al, 2016].…”
Section: Introductionmentioning
confidence: 99%